2022
DOI: 10.3389/fcell.2022.813043
|View full text |Cite
|
Sign up to set email alerts
|

A Prognostic Model Using Immune-Related Genes for Colorectal Cancer

Abstract: There is evidence suggesting that immune genes play pivotal roles in the development and progression of colorectal cancer (CRC). Colorectal carcinoma patient data from The Cancer Genome Atlas (TCGA) and the Gene Expression Omnibus (GEO) were randomly classified into a training set, a test set, and an external validation set. Differentially expressed gene (DEG) analyses, univariate Cox regression, and the least absolute shrinkage and selection operator (LASSO) were used to identify survival-associated immune ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…For instance, Tan et al constructed a 9 IRG panel in triple-negative breast cancer (TNBC), and the related nomogram could assess the axillary lymph node (ALN) status preoperatively with better predictive ability than the IRG model alone 23 . Feng et al revealed that 14 IRGs were correlated with the OS of patients with colorectal cancer (CRC) after chemotherapy, and the constructed model could predict immune status and chemotherapy sensitivity 24 . Consistent with these studies, our risk model was an independent prognostic indicator with higher prognostic efficiency in evaluating OS of BC than other independent clinicopathological variables, including age, clinical stage, and TNM stage.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Tan et al constructed a 9 IRG panel in triple-negative breast cancer (TNBC), and the related nomogram could assess the axillary lymph node (ALN) status preoperatively with better predictive ability than the IRG model alone 23 . Feng et al revealed that 14 IRGs were correlated with the OS of patients with colorectal cancer (CRC) after chemotherapy, and the constructed model could predict immune status and chemotherapy sensitivity 24 . Consistent with these studies, our risk model was an independent prognostic indicator with higher prognostic efficiency in evaluating OS of BC than other independent clinicopathological variables, including age, clinical stage, and TNM stage.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the most highly up-regulated gene products in our analysis included MMP7, PPBP, and CXCL5. Prior work by others has identified the MMP7 ( Gao et al, 2019 ; Huang et al, 2021 ; Vočka et al, 2019 ), PPBP ( Chen et al, 2022 ; Kothalawala & Győrffy, 2023 ; Feng et al, 2022 ), and CXCL5 gene products to be extremely useful in the mechanisms and diagnosis of colorectal cancer ( Chen et al, 2019 ; Zhang et al, 2021 ; Novillo et al, 2020 ; Zhang et al, 2020 ). We also identified multiple down-regulated genes in colorectal cancer that are supported by recent studies on the gene products of the OTOP2 ( Qu et al, 2019 ; Yang & Sakharkar, 2022 ), OTOP3 ( Yang & Sakharkar, 2022 ), SPIB ( Zhao et al, 2021 ; Liu et al, 2019 ), and INSL5 genes ( Yang et al, 2021c ; Sun et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%